2008
DOI: 10.1089/hum.2008.067
|View full text |Cite
|
Sign up to set email alerts
|

A Negatively Acting Bifunctional RNA Increases Survival Motor Neuron Both In Vitro and In Vivo

Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive neuromuscular disorder and is the leading genetic cause of infant mortality. SMA is caused by the loss of survival motor neuron-1 (SMN1). In humans, a nearly identical copy gene is present called SMN2, but this gene cannot compensate for the loss of SMN1 because of a single silent nucleotide difference in SMN2 exon 7. This single-nucleotide difference attenuates an exonic splice enhancer, resulting in the production of an alternatively spliced isoform lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 49 publications
1
29
0
1
Order By: Relevance
“…These include small molecules to augment SMN2 transcription, correct SMN2 splicing, cause translational readthrough, and stabilize SMN2 transcripts (Lunn and Wang, 2008); SMN gene delivery to replace SMN protein (Foust et al, 2010;Passini et al, 2010); antisense oligonucleotide (ASO)-based approaches to correct SMN2 splicing (Lim and Hertel, 2001;Miyajima et al, 2002;Cartegni and Krainer, 2003;Skordis et al, 2003;Singh et al, 2006;Hua et al, 2007Hua et al, , 2008Hua et al, , 2011Dickson et al, 2008;Williams et al, 2009;Osman et al, 2012;Porensky et al, 2012;Mitrpant et al, 2013;Zhou et al, 2013); and antisense-producing vector-based strategies (Geib and Hertel, 2009;Meyer et al, 2009), including trans-splicing (Coady et al, 2007;Coady and Lorson, 2010). Some of these strategies have not yet been tested in animal models of SMA, but others have already been shown to be beneficial (Bebee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These include small molecules to augment SMN2 transcription, correct SMN2 splicing, cause translational readthrough, and stabilize SMN2 transcripts (Lunn and Wang, 2008); SMN gene delivery to replace SMN protein (Foust et al, 2010;Passini et al, 2010); antisense oligonucleotide (ASO)-based approaches to correct SMN2 splicing (Lim and Hertel, 2001;Miyajima et al, 2002;Cartegni and Krainer, 2003;Skordis et al, 2003;Singh et al, 2006;Hua et al, 2007Hua et al, , 2008Hua et al, , 2011Dickson et al, 2008;Williams et al, 2009;Osman et al, 2012;Porensky et al, 2012;Mitrpant et al, 2013;Zhou et al, 2013); and antisense-producing vector-based strategies (Geib and Hertel, 2009;Meyer et al, 2009), including trans-splicing (Coady et al, 2007;Coady and Lorson, 2010). Some of these strategies have not yet been tested in animal models of SMA, but others have already been shown to be beneficial (Bebee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This promising perspective seems to be greatly boosted by recent developments in SMN/SMA studies in which technologies such as trans-splicing, bifunctional oligonucleotides, and anti-sense oligonucleotides very specifically increase the inclusion of exon 7 into SMN2 mRNA (Fig. 2) (Baughan et al, 2006;Coady and Lorson, 2010;Coady et al, 2007;Dickson et al, 2008;Hua et al, 2010;Lorson et al, 2010;Osman et al, 2012;Shababi and Lorson, 2011;Shababi et al, 2011;Skordis et al, 2003). In particular, the effectiveness of anti-sense oligos in animals with SMA has excited the scientific community so that SMA may be treatable in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…Bifunctional oligoribonucleotides effectively increase insertion of exon 7 into SMN2 mRNA. Relative to bifunctional oligoribonucleotides (Baughan et al, 2006;Dickson et al, 2008;Horne and Young 2009;Osman et al, 2012;Skordis et al, 2003;Voigt et al, 2010), the strategy of trans-splicing is new but has offered great promise to correct abnormal splicing of several other genes (Coady et al, 2007;Puttaraju et al, 1999;Rodriguez-Martin et al, 2005). Trans-splicing is based on studies showing that two pre-mRNAs can undergo transsplicing if sufficient homologies between the two pre-mRNAs exist, leading to the first part of the mRNA from exons of premRNA1 and the second part from exons of pre-mRNA2.…”
Section: Sma Animal Modelsmentioning
confidence: 99%
“…Several in vivo studies have shown increased SMN2 protein levels after intraventricular injection of splicing factors recruiting AONs (Dickson et al, 2008;Baughan et al, 2009). …”
Section: Modulating Pre-mrna Splicingmentioning
confidence: 99%